Four novel strains of cellulolytic symbiotic bacteria isolated and characterized from GI tract of marine fishes of various feeding habits. (October 2018) - Augustine, Asha; Joseph, Imelda
Abstract: Selected marine fishes with different feeding habits were screened for the presence of symbiotic cellulolytic bacteria in their gut. Four cellulolytic species of symbiotic bacteria were isolated from GI tract of marine fishes namely Carangoides praeustus, Filimanus similis, Sardinella longiceps and Sillago sihama . The strains were identified after polyphasic phenotypic and genotypic (16S rRNA gene) characterization as Bacillus subtilis strain TCPC1, Vibrio alginolyticus strain CFSS2C2, Pseudomonas stutzeri strain KSLS4C3 and Klebsiella oxytoca strain MSSC4. (Genbank Accession nos.: JN710380, JN710378, JN710377, JN712301).The results indicated the presence of cellulolytic bacteria in GI tract of marine fishes of carnivorous, phytoplanktivorous and omnivorous feeding habits. Cellulolytic activity was the maximum for B. subtilis strain TCPC1 (0.45 mg glucose ml −1 ) and V. alginolyticus strain CFSS2C2 (0.24 mg glucose ml −1 ) at 234 h. While P. stutzeri strain KSLS4C3 showed the maximum utilization (0.22 mg glucose ml −1 ) from 240 to 258 h. K. oxytoca strain MSSC4 (0.47 mg glucose ml −1 ) showed three peaks during the study. The maximum rate of cellulose utilization was shown by P. stutzeri strain KSLS4C3 (0.05 mg glucose ml −1 medium h −1 ) followed by K. oxytoca strain MSSC4 (0.03 mg glucose ml −1 medium h −1 ). Highlights: Novel strains of cellulolyic bacteria from unconventional sources like gut of marine fishes If other energy sources are available, a potential cellulase producer may not utilize cellulose. The process should be perfected for maximization of enzyme production at minimum cost and time.